Root distribution of Adansonia digitata, Faidherbia albida and Borassus akeassii along a climate gradient in Senegal - (:unkn) unknown (My University, 2023)
In order to understand the ecophysiology of sub-Sahelian tree species and to optimize their use in agroforestry, studies on tree root distribution are essential. The aim of this study was to investigate the root distribution of three sub-Sahelian tree species, Adansonia digitata, Faidherbia albida and Borassus akeassii, in three sites along a precipitation and soil gradient in Senegal. Root density maps observed on trench walls and soil-coring methods were used to characterize variations in root density of mature trees. Coarse and fine root distribution was strongly influenced by the site conditions, with root density being highest in the humid site for all tree species. B. akeassii had the highest root density compared to the other two species. Fine root biomass was concentrated in the 0-30 cm soil layer for A. digitata and from 30 to 60 cm for B. akeassii and F. albida. Laterally, the fine root biomass decreased substantially with increasing distance from the trees. Understanding the root distribution of sub-Sahelian tree species across climatic conditions could help to reduce competition between crops and perennials in agroforestry parklands.
Keywords: African Research